Sunbeds with UVB radiation can produce physiological levels of serum 25-Hydroxyvitamin D in healthy volunteers. Issue 1 (1st January 2017) - Kimball, Samantha M.; Lee, Jasmine; Vieth, Reinhold
ABSTRACT: Vitamin D3 is produced in the skin in response to UVB irradiation, from either sun exposure or UVB sunbeds. The objective of the current study was to characterize serum 25(OH)D response to regular sunbed use from several lamp outputs following their respective time exposure recommendations. There were three groups that tanned over 12 weeks during the winter months in dedicated sunbeds based on lamp outputs (100 W and 160 W low pressure fluorescent and 700 W high pressure filtered metal halide lamps) and a control group provided serum 25(OH)D samples at baseline and end-of-study. Tanning session lengths were calculated based on Health Canada guidelines to stay below the erythema levels. Mean 25(OH)D were increased by an average of 42 nmol/L in the sunbeds that used 100 W and 160 W fluorescents. Change in 25(OH)D was dependent on baseline 25(OH)D levels and sunbed (p = 0.003) and age (p = 0.03), but was not affected by gender, BMI, Fitzpatrick type or cumulative length of tanning sessions. There was no significant increase in 25(OH)D levels in participants using the 700 W filtered metal halide lamp sunbed or in the control participants. Skin pigmentation, ITA °, was markedly increased in all tanners and skin lightness, L*, significantly decreased at 12 weeks. Both L* andITA ° were significantly correlated with 25(OH)D concentrations for the sunbeds with fluorescent lamps emitting UVB (100 W and 160W). Participants following standardized exposure schedules meeting Health Canada regulations in sunbeds irradiating adequate UVB showed continuous increases of 25(OH)D to physiological levels even after producing a tan in a controlled manner. ClinicalTrials.gov Registration: NCT02334592